Licet interdum confabulationis tale conuiuium doctrinae quoque sale condiatur: Jerome’s letters to Marcella, and biblical exegesis in epistolary form (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
In this paper we try to highlight the variety of epistolary ‘topoi’ found in the letters of the Ad Marcellam Liber, especially those of exegetical content, quickly comparing them with the (much more varied) typologies found in Jerome's only other epistolary liber, the Ad diuersos epistularum liber. We then attempt to focus on the first paragraph of Ep. 29, addressed to Marcella and of exegetical content, illustrating in their context the two metaphors of epistolary discussion and exegetical content as nourishment for the soul. Finally, comparisons for similar food metaphors in Jerome’s other letters and with pagan and Christian Latin epistles are sought, highlighting Jerome's sobriety (compared to the refinement of Paulinus of Nola) but also his penchant for using such metaphors, which are apparently less numerous in Ambrose and Augustine, as well as in pagan epistles.